An open source peridynamics code for dynamic fracture in homogeneous and heterogeneous materials. (June 2022) - Jenabidehkordi, Ali; Fu, Xiaolong; Rabczuk, Timon
Highlights: We propose an open source code for meshfree computational methods, especially peridynamics. The code is based on objective oriented programming (OOP) and a relation based architecture (RBS). The open source code can deal efficiently with complex geometries. The performance of the code is demonstrated through several benchmark problems. Abstract: We present a novel open source peridynamics software for modeling two- and three-dimensional dynamic fracture in homogeneous and heterogeneous solids. The software and its implementation is described in detail and made available on GitHub and under MIT license. The capability of the software is demonstrated through several numerical examples including a wave propagation problem. Furthermore, 3D fracture simulations in a polymer-matrix composite at the meso-scale is shown to demonstrate the capability of the code to model complex microstructure including the interaction between interface fracture and fracture in the bulk.